2020
DOI: 10.1089/cyber.2019.0205
|View full text |Cite
|
Sign up to set email alerts
|

How Social Cues in Virtual Assistants Influence Concerns and Persuasion: The Role of Voice and a Human Name

Abstract: The aim of this study was to test how two important types of social cues used by virtual assistants today can affect consumer concerns and persuasion. These two cues are modality (voice-based via smart speaker, voicebased via a smartphone, or text-based on a smartphone screen) and the adoption of a human name rather than no name. An online scenario-based experiment (n = 180) has shown that participants who were exposed to a voicebased recommendation via a smart speaker were the most concerned about security an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 46 publications
1
7
1
Order By: Relevance
“…It thereby shows that findings from these research lines can be translated to the context of virtual assistants. Hence, we can show and corroborate previous research (Voorveld and Araujo, 2020) that using the persuasion knowledge model is generally a useful tool to explain persuasive attempts coming from a virtual assistant. Notably, the positive effects of persuasion knowledge on brand memory were stronger than the negative effects on brand attitudes and purchase intention.…”
Section: Discussionsupporting
confidence: 89%
“…It thereby shows that findings from these research lines can be translated to the context of virtual assistants. Hence, we can show and corroborate previous research (Voorveld and Araujo, 2020) that using the persuasion knowledge model is generally a useful tool to explain persuasive attempts coming from a virtual assistant. Notably, the positive effects of persuasion knowledge on brand memory were stronger than the negative effects on brand attitudes and purchase intention.…”
Section: Discussionsupporting
confidence: 89%
“…Because research has demonstrated that voice assistants have a bad reputation concerning a lack of transparency on how data is processed and stored ( Voorveld and Araujo, 2020 ), the missing effect of ontological class on the privacy concerns was surprising. However, the companies behind the state-of-the-art voice assistants are also frequently the reasons for mistrust ( Lau et al, 2018 ), which was not the case within this study as the voice assistant was presented as a product of a university research project.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be highlighted that different technologies are associated with different privacy concerns. Voorveld and Araujo (2020) , for instance, demonstrated that interactions via smart speakers created higher data security concerns compared to the same interactions with a voice assistant on a smartphone. The authors discuss that this might be due to the fact that voice within the voice assistant is designed to continuously “listen” to users.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…Recently, studies have been conducted that demonstrated the modality of algorithm-mediated communication (e.g. voice vs. text) plays a role in its persuasive impact on recipients (Cho, 2019;Cho et al, 2019;Voorveld and Araujo, 2020). This implies that modality should be considered in the investigation of outcomes of algorithm-mediated communication.…”
Section: The Input: Datamentioning
confidence: 99%
“…Theories like the MAIN model (Sundar, 2008), and the cognitive theory of multimedia learning (Mayer, 2014) acknowledged the importance of modality in shaping communication effects. Recently, studies have been conducted that demonstrated the modality of algorithm-mediated communication (e.g., voice vs. text) plays a role in its persuasive impact on recipients (Cho, 2019;Cho et al, 2019;Voorveld and Araujo, 2020). This implies that modality should be considered in the investigation of outcomes of algorithm-mediated communication.…”
Section: The Persuasion Attempt: Context Nature Medium and Modalitymentioning
confidence: 99%